Respostas

2013-06-01T17:40:04-03:00

Usa-se de bascara

 

6² - 4.9.(-48)

1764

 

(-6 +- V1764)/18

 

-6+- 42/18

 

x1= -48/18 = -2,6...

x2= 36/18 = 2

Espero ter ajudado =)

1 4 1
2013-06-01T18:03:12-03:00

Olá!!!

Sabemos que:

a=9

b=6

c=-48

Basta usar baskara

 

x=\frac{-b\frac{+}{}\sqrt{b^2-4.a.c}} {2.a}\\ \\ x=\frac{-6\frac{+}{}\sqrt{6^2-4.9.(-48)}} {2.9}\\ \\ x=\frac{-6\frac{+}{}\sqrt{36-36.(-48)}} {18}\\ \\ x=\frac{-6\frac{+}{}\sqrt{36-(-1728)}} {18}\\ \\ x=\frac{-6\frac{+}{}\sqrt{1764}} {18}\\ \\ x=\frac{-6\frac{+}{}42} {18}\\ \\ x^1=\frac{-6+42}{18}=2\\ \\ x^2=\frac{-6-42}{18}=-2,66...